The role of resilience in explaining hotel growth: A fuzzy-set QCA approach - Diana Dryglas; Anna Lis; Marcin Suder (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: Due to the detrimental effects of the recent pandemic on the hotel sector, hotel resilience research and its impact on hotel recovery have received lots of academic attention. However, a sustainable perspective on hotel resilience, as an approach for investigating its impact on long-term hotel growth, has been largely overlooked in the hospitality resilience literature. Therefore, this paper aims to address the research gap by identifying the configuration of factors that constitute sustainable hotel resilience, leading to the growth of selected hotels operating in Poland. METHODOLOGY: Data for analysis were obtained from surveys conducted with 120 managers of one- and two-star hotels. A fuzzy-set qualitative comparative analysis (fsQCA) was chosen to achieve the goal, which belongs to the group of configurational analysis methods. FINDINGS: Due to the asymmetric nature of the method, the analysis reveals configurations of factors leading to high hotel growth and those leading to low growth. In both cases, two such factor configurations were obtained. For high levels of hotel growth, it was found that maintaining a high level of three factors simultaneously, namely employee resilience, CSR activities and leadership resilience or CSR activities, team resilience and leadership resilience, provided sufficient conditions. For low levels of growth, fsQCA indicated sufficient conditions in the form of a low level of CSR activities and leadership resilience or a low level of employee resilience and team resilience. These findings emphasize the role of combining different factors to improve hotel growth. IMPLICATIONS: The research contributes to the literature on resilience in the hospitality industry by developing a new theoretical perspective on the complex nature of combinations of factors that contribute to sustainable hotel resilience, leading to both high and low growth. The research results also provide significant implications for entrepreneurs and managers, indicating the role of different combinations of factors in determining hotel growth. ORIGINALITY AND VALUE: The knowledge regarding sustainable hotel resilience is still insufficient. The study identified the best combinations of factors (both internal and external) that constitute sustainable hotel resilience, which may be vital for hotel growth.